Management of Zakat as the Instrument to Improve Economic Recession of COVID-19 - Mursyidi Abror; Muhammad Nafik Hadi (AFEBI Islamic Finance and Economic Review, 2020)
The purpose of ziswaf management is to restore the chaotic condition of the country due to Covid-19, especially in the economic sector. The purpose of this research is to analyze how the mechanism and implementation of zakat distribution in response to the Covid-19 pandemic. The method used is literature study method. The literature study in this research is technical literature and non-technical literature. Based on the results of the analysis, BAZNAS has distributed zakat funds to three sectors, namely the field of health emergencies, socio-economic emergencies, and the field of existing program sustainability. From the results of this analysis, it can be concluded that the handlers of zakat implementation in handling Covid 19 have a very big influence. The total distribution of funds for the three sectors reached Rp. 7,578,461,063.Keyword: Ziswaf, Economics, Covid-19